Designing a Web-Based Management Information System for Incoming and Outgoing Mail at the Public Welfare Bureau of the North Sumatra Provincial Secretariat - Hengki Gunawan; Barany Fachri; Fahmi Kurniawan (CV. AFDIFAL MAJU BERKAH, 2025)
The management of incoming and outgoing mail at the Public Welfare Bureau of the North Sumatra Provincial Secretariat is currently done manually by recording it in an agenda book. Mail distribution is also done directly, and mail archiving is collected in one place, which often causes various problems, such as delays in mail distribution, difficulties in finding mail, and the risk of losing important mail. This study aims to design and develop a web-based document management system to support more efficient, faster, and secure administrative processes. The system development method used is the waterfall model. The system is built using the PHP programming language and MySQL database. System testing results indicate that it can simplify the processes of recording, searching, distributing, and reporting incoming and outgoing documents through faster digitalization. With the implementation of this system, it is hoped that the Social Welfare Bureau of the Provincial Government of North Sumatra can manage letters more effectively and efficiently, thereby supporting the central government's digital transformation program